HUBUNGAN KOMUNIKASI INTERPERSONAL DENGAN PENYESUAIAN DIRI SISWA KELAS VII DI SMP NEGERI 17 KOTA JAMBI - Haryati, Tutik (Jurnal Kopendik, 2022)
This study aims to: 1) Reveal the quality of interpersonal communication of class VII students at SMP Negeri 17 Jambi City 2). Revealing the quality of adjustment of class VII students at SMP Negeri 17 Jambi City 3). Revealing the relationship between interpersonal communication and adjustment of class VII students at SMP Negeri 17 Jambi City. The type of research conducted by researchers is classified as correlational. quantitative approach. The population in this study is interpersonal communication and adjustment of class VII students at SMP Negeri 17 Jambi City in the 2017/2018 academic year. The sampling technique used is Simple Random Sampling. This formula is used to test and reveal the quality of interpersonal communication and adjustment in class VII students at SMP Negeri 17 Jambi City, then the data from the student questionnaire answers obtained will be analyzed using the percentage technique. Percentage analysis that has been done on each research variable, it is known that students' interpersonal communication with a weighted value obtained is 1398 and the average percentage value obtained is 75.7%. So it can be concluded that the quality of interpersonal communication of class VII students at SMP Negeri 17 Jambi City is of good quality